Feasibility and efficacy of a digital resilience training: A pilot study of the strengths-based training RESIST - Behrendt, Dörte; Boß, Leif; Hannibal, Sandy; Kunzler, Angela M.; Wessa, Michèle; Lehr, Dirk (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Background: Work-related stress is a risk factor for a number of adverse health and work outcomes. Resilience trainings are a promising approach for adequately dealing with work stress and keeping employees mentally healthy. However, results of previous resilience trainings have been heterogeneous, ranging from null findings to large effects. Existing digital resilience interventions show a lack of consistency in terms of an underlying theoretical framework and methods used to foster resilience. Positive Appraisal Style Theory of Resilience offers an innovative conceptualization of resilience. Strengths-based cognitive behavioral therapy is a corresponding therapeutically method reflecting resilience as a resource-oriented process of dealing with stress. Based on this background, a new hybrid web-and app-based digital resilience intervention for employees named RESIST was developed. Objective: The first aim of the study was to investigate the feasibility of the newly developed training RESIST regarding its usability, user behavior, user experience and motivation to use. Second, the study sought to explore preliminary effects of the intervention on reducing stress and enhancing resilience by conducting a pilot randomized controlled trial. Methods: The feasibility study was conducted in three phases. First, the usability of the app was investigated in a pre-test with five participants using a thinking-aloud method. Second, the preliminary efficacy of the training was examined in a pilot randomized controlled trial. A sample of 30 employees were randomized either to receive the resilience training (n = 15) or to be member of a control group (n = 15). The primary outcome was measuring perceived stress. Secondary outcomes included measures of resilience and depressive symptoms. Third, semi-structured interviews were undertaken with six participants of the resilience training group on training content, motivation for use, and user experience. Results: Overall, results indicate that RESIST can be a feasible training for resilience promotion and stress reduction with high user satisfaction. Analysis of covariance showed that, relative to controls, participants who received RESIST reported significantly lower stress scores at post-intervention (F1,27 = 16.91, p < 0.001; Cohen's d = 1.57; 95 % CI 0.71–2.43) than controls. Significant differences, with moderate-to-large effect sizes, were also detected for general resilience and various resilience factors. Conclusions: Results are promising and provide hope that a hybrid web- and app-based resilience intervention based on strengths-based cognitive behavioral therapy can have a positive impact on dealing adequately with stress and improve resilience of employees.
Keywords: App; Digital; Training; Resilience; Feasibility; Strength; Cognitive Behavior; Therapy